Using growth and geochemical composition of Clathromorphum compactum to track multiscale North Atlantic hydro-climate variability - Siebert, Valentin; Poitevin, Pierre; Chauvaud, Laurent; Schöne, Bernd R.; Lazure, Pascal; Thébault, Julien (Palaeogeography, Palaeoclimatology, Palaeoecology, 2020)
International audience Records of ocean/atmosphere dynamics over the past centuries are essential to understand processes driving climate variability. This is particularly true for the Northwest Atlantic which is a key region with an essential role in global climate regulation. Over the past two decades, coralline red algae have been increasingly used as environmental and climatic archives for the marine realm and hold the potential to extend long-term instrumental measurements. Here, we investigate the possibility to extract climate and environmental information from annual growth patterns and geochemical composition of the coralline red algae, Clathromorphum compactum, from Saint-Pierre & Miquelon (SPM), a French archipelago southwest of Newfoundland. However, measurements of C. compactum growth trends is challenging due to difficulties in identifying annual growth lines directly. So far, growth pattern investigations were commonly performed based on geochemical data of coralline calcite matrix. Nonetheless, this method is expensive and therefore prevents from analyzing a large number of specimens that would be representative of the population. For this reason, we enhanced the growth line readability by staining polished sections with Mutvei's solution and performed growth analysis based on direct increment width measurements. Geochemical analyses were also carried out in order to validate the assumption that growth lines observed after staining were formed on an annual basis. Moreover, growth pattern and trace element composition were measured on multiple axes of several individuals in order to assess the intra- and inter-specimen variability and validate their use for paleoenvironmental reconstructions. Finally, relationships between the C. compactum sclerochronological records from SPM and environmental datasets covering different geographical areas allow a better knowledge of flow dynamics in the Northwest Atlantic and confirm the findings related to Arctica islandica from the same location.